KEMAMPUAN BERPIKIR KREATIF SISWA DALAM GEOMETRIC DISSECTIONS MATERI SEGI EMPAT DI SEKOLAH MENGENGAH PERTAMA - Ruzniar, Riza; Sugiatno, Sugiatno; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractStudentâ€™s creative thinking ability is essential to be developed in national education practice. In fact, studentâ€™s creative thinking ability didnâ€™t get serious attention even in school and national level. Even though, creative thinking is one of Â standards that have been stated in every curriculum. So, this study aimed to explain studentâ€™s creative thinking ability to solve Geometric Dissection puzzle in dissecting rectangle into square. The research method was descriptive and research design was survey. The subject of this research was 44 students of VIII E SMP Negeri 21 Pontianak. The result showed that there were 4 of 5 levels of studentâ€™s creative thinking ability. There were 16 (36,36%) students with â€œthe most creativeâ€ thinking level, 20 (45,45%) students with â€œcreativeâ€ thinking level, 7 (15,91%) students with â€œmoderate creativeâ€ thinking level, and 1 (2,27%) students with â€œnot creativeâ€ thinking level. In fluency aspect of creative thinking, there were 36 (82%) students qualify and 8 (18%) students didnâ€™t. In flexibility aspect of creative thinking, there were 16 (36%) students qualify and 28 (64%) students didnâ€™t. In originality aspect of creative thinking, there were 43 (98%) students qualify and 1 (2%) students didnâ€™t.Â Keywords: Creative thinking ability, Geometric Dissections, Rectangle to square